Fixed-interval pause duration in chained fixed-ratio, fixed-interval schedules - Todorov, João Claudio (2017)
Ten rats were submitted to chained fixed-ratio (FR), fixed-interval (FI) schedules of reinforcement. A FR schedule at one lever produced a discriminative stimulus associated with a FI 60-s schedule of primary reinforcement (water) at the second response lever. In Experiment 1, the FI schedule was kept constant while the FR requirement was changed from one to seven responses under five different experimental conditions for five rats. Increases in the FR requirement resulted in increases in post-reinforcement pauses but also decreases in pauses in the FI schedule. Using another five rats, Experiment 2 tested the hypothesis that short pauses in the FI schedule result from the use of the chained schedules procedure. Baseline was a FI 80-s schedule. In the second condition, chained FR 1 FI 80-s schedules were programmed. The third condition was a return to baseline. In baselines 1 and 2, the FI pause was compatible with the literature but decreased considerably when a chained schedule was used. The present results support the hypothesis that the time between primary reinforcement presentations dominates the control of FI pauses over control by the onset of a discriminative stimulus.